Pemahaman Manajemen Tentang Peraturan Perpajakan Dalam Hubungannya Dengan Kepatuhan Wajib Pajak Badan (Studi Kasus pada KPP Tanjung Karang) - Syamsu Rizal; Nia Fitri Sari; Haninun HANINUN (Jurnal Akuntansi dan Keuangan, 2012)
As for the purpose and benefits of this research is to know the extent to which the understanding of management are registered on the KPP Pratama Tanjung Karang in understanding taxation regulations in Cape Coral and to analyze the relationship between managements understanding of the KPP Pratama Tanjung is listed on the Reef about compliance with tax regulations tax payers of existing agencies in Cape Coral as well as add insight/understanding of taxation regulations against the Taxpayers compliance with the Agency. Based on the above issues, then set the following hypothesis:% u201CTerdapat relationship between managements understanding of the law No. 36 year 2008 against Taxpayer compliance Agency on law No. 28 of 2007